MELATONIN IMPLANT INDUCES ESTRUS AND ALLEVIATES OXIDATIVE STRESS IN SUMMER ANESTRUS BUFFALO - SINGH, B; GHUMAN, SPS; CHEEMA, RS; BANSAL, AK (The Indian Journal of Animal Reproduction, 2016)
Summer anestrus buffalo were divided into control (n=29) and treatment group (n=41). Treated buffalo were subcutaneously inserted melatonin implants @18mg/50kg body wt. Estrus signs were observed till 35 days post-treatment and estrus induction rate (%) was recorded. Blood samples were collected at weekly intervals, 7 days prior to insertion of implant until day 35 after insertion of implant. Estrus induction rate was higher (χ2=3.19, p
Keywords: Buffalo; Melatonin Implant; Oxidative stress; Summer Anestrus